Conveyor-belts of information: the role of political parties in basic service delivery in Africa - Krönke, Matthias (Department of Political Studies, 2024)
Despite a growing interest, African political parties have received relatively little attention beyond their role as providers of clientelistic goods and services. Yet, they also regularly transmit large amounts of information about government performance between the state and its citizens. In this dissertation, I aim to fill this gap in the literature by asking whether political parties matter for how citizens view the delivery of basic government services? I argue that where political parties collect, process, and share information about government service delivery between citizens and bureaucrats, citizens are more satisfied with said services, even where the provision is objectively the same. To illustrate political parties' role as Conveyor-Belts of Information, I focus specifically on two types of actors in these organisations – local party activists and elected representatives. First, using a panel survey of Zambian citizens I demonstrate that party activists and elected officials operate as ambassadors, advocates, and problem solvers, continuously exchanging information with citizens about service delivery during and between elections. Second, I use surveys of Malawian party elites and bureaucrats to show the inner workings of political parties as conveyor-belts of information that seek to improve citizen experience with service delivery. Third, I employ public opinion data from over 30 African countries, and surveys of more than 800 elected representatives from 17 countries to demonstrate under which conditions political parties increase citizens' satisfaction with service delivery. Ultimately, I find that African parties play an important role for citizens' satisfaction with basic services in general, and particularly for education, and health care. Further, I show that this mechanism not only applies to ruling, but occasionally also to opposition parties. The findings of this study have important implications for our understanding of how political parties contribute to democratic accountability in Africa. For example, the findings suggest that African political parties may be far more important for the transmission of information between the state and its citizens than we have previously believed.